Efektivitas Peraturan Menteri Kesehatan Nomor 23 Tahun 2021 tentang Pelaksanaan Vaksinasi dalam Rangka Penanggulangan Pandemi Covid-19 terhadap Capaian Vaksinasi di Kota Padang - Jantarda Mauli Hutagalung; Clara Ignatia Tobing (Universitas Kuningan, 2022)
COVID-19 has become a global threat that affects most countries in the world. The existence of COVID-19 has pressured and pushed the Government to do something to at least reduce the number of virus spread and reduce the death rate. One of the programs made by the Government is to carry out the COVID-19 vaccination to create herd immunity in Indonesian society. To create herd immunity, at least 70% of the Indonesian population is included in the COVID-19 vaccine target. This is then used as a target for achieving COVID-19 vaccination. In order to accelerate vaccination, the government issued various related regulations. The city of Padang which is the capital city of West Sumatra Province is included in the province with the lowest achievement. This study aims to see the effectiveness of the rules on the achievement of vaccination in the city of Padang. The method used in this research is quantitative juridical research. Through searching secondary data by analyzing data on the first and second doses of COVID-19 vaccination in the city of Padang. The results of the analysis will then show that the existing regulations have an effective effect in increasing the number of COVID-19 vaccination achievements in the city of Padang.